2019
DOI: 10.17352/gjz.000011
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal spatial distribution of aedes aegypti (Diptera: Culicidae) during the yellow fever epidemic in Angola, 2016

Abstract: Background and aims:Angola is one of the countries included in the endemic areas of yellow fever transmission in Africa. The objective of this study was to obtain information about the longitudinal spatial distribution and the mainly breeding sites of Ae. aegypti in Angola during the yellow fever epidemic in Angola during 2016.Methods: Angola is located in the western region of Southern Africa. The country limited by the Atlantic Ocean in the west, in the north with the Republic of Congo and the Democratic Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Indeed, between 2015 and 2016 in Central Africa, major urban YF outbreaks occurred in Angola and Democratic Republic of Congo with 7,334 suspected cases, of which 962 have been confirmed, and 393 deaths [6]. Aedes aegypti was suspected as the main YFV vector involved during the Angola outbreak due to its high densities reported across the country [7]. On the other hand, recent studies on entomological surveillance in Central Africa particularly in Cameroon [8] and the Republic of Congo [9], where sporadic cases of YF were frequently reported, showed that Ae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, between 2015 and 2016 in Central Africa, major urban YF outbreaks occurred in Angola and Democratic Republic of Congo with 7,334 suspected cases, of which 962 have been confirmed, and 393 deaths [6]. Aedes aegypti was suspected as the main YFV vector involved during the Angola outbreak due to its high densities reported across the country [7]. On the other hand, recent studies on entomological surveillance in Central Africa particularly in Cameroon [8] and the Republic of Congo [9], where sporadic cases of YF were frequently reported, showed that Ae.…”
Section: Introductionmentioning
confidence: 99%
“…luteocephalus . From 2010 to 2016, 13,837 suspected cases of YF were reported of which 109 cases were confirmed with 66% mostly in rural areas [7]. The epidemiological importance of both vectors in urban YFV transmission in Central Africa has not been assessed precisely up to now.…”
Section: Introductionmentioning
confidence: 99%